Factors related to the diagnosis of lung cancer by transbronchial biopsy with endobronchial ultrasonography and a guide sheath. Issue 24 (20th October 2022) - Kurihara, Yuki; Tashiro, Hiroki; Takahashi, Koichiro; Tajiri, Ryo; Kuwahara, Yuki; Kajiwara, Kokoro; Komiya, Natsuko; Ogusu, Shinsuke; Nakashima, Chiho; Nakamura, Tomomi; Kimura, Shinya; Sueoka‐Aragane, Naoko
Abstract: Background: Transbronchial biopsy (TBB) with endobronchial ultrasonography and a guide sheath (EBUS‐GS) is an effective examination tool for the diagnosis of lung cancer. Factors related to making the diagnosis are still not fully understood. Methods: A total of 367 patients who underwent EBUS‐GS and were diagnosed with lung cancer in Saga University Hospital were investigated retrospectively. Clinical characteristics were compared between 244 patients who were diagnosed with lung cancer and 123 patients who were not diagnosed by TBB with EBUS‐GS but were diagnosed by other examinations. Results: Size of target lesion, rate of patients with target lesion size ≥20 mm, presence of the bronchus sign, and detection by EBUS imaging were significantly associated with making the diagnosis (all p < 0.01). In patients whose lesion was detected by EBUS imaging, patients with positive findings within the lesion were significantly more often diagnosed by TBB with EBUS‐GS than those with positive findings adjacent to the lesion ( p < 0.01). The odds ratio (OR) of patients whose lesion was detected by EBUS imaging (OR [95% confidence interval] 14.5 [8.0–26.4]) tended to be higher compared to the ORs of size of lesion ≥20 mm (3.9 [2.2–6.8]) and the bronchus sign (7.5 [4.6–12.2]). Conclusion: Targeted lesion diameter ≥20 mm, bronchus sign, and detection by EBUS imaging, especially within the lesion, are important factors for the diagnosis of lung cancer by TBB with EBUS‐GS. Abstract : The present study showed that size of targeted lesion, especially diameter ≥20 mm, the bronchus sign, and detection on EBUS imaging were significant contributors to making the diagnosis of lung cancer by TBB with EBUS‐GS. In addition, the odds ratio (OR) of detection on EBUS imaging for the diagnosis of lung cancer with EBUS‐GS tended to be higher than the ORs of other factors, including targeted lesions >20 mm and the bronchus sign. According to these data, detection on EBUS imaging, especially within the lesion, is important for the diagnosis by TBB with EBUS‐GS.